Liveworksheet-Assisted Ipas E-Lkpd Development To Improve Learning Outcomes Of Class V Students Sd Negeri 064990 Medan Johor - Ruspiana Hutagaol; Wildansyah Lubis; Sugiharto Sugiharto (UNIVERSITAS PAKUAN, 2025)
This research aims to develop an e-LKPD IPAS assisted by liveworksheets that is effective in improving the learning outcomes of grade V students of SD Negeri 064990 Medan Johor. This type of research is Research and Development (RD) using the 4D development model, which consists of four stages: (1) Define; (2) Design; (3) Development; and (4) Dissemination. The findings of this study are: The effectiveness of e-LKPD IPAS was evaluated by the results of the gain test of 0.69 included in the